(untitled) - Wines-Reed, Jeanne (Indianapolis, IN, 2007)
Scrapbooking For Dummies is perfect for you if you’re a new scrapbooker who wants to create your own personal scrapbook (or who would like to make a special scrapbook for a friend or loved one) or if you’re already an avid scrapbooker who’s looking for helpful tips and new ideas. This friendly guide takes the guesswork out of creating well-designed albums.
Keywords: Photograph albums,Photographs,Scrapbooking,Album ảnh,Ảnh,Sách ảnh cắt nhỏ; Conservation and restoration,Bảo tồn và phục hồi